78.9k views
2 votes
I need to use multi-step inverses with logs:

I need to use multi-step inverses with logs:-example-1
User MBL
by
5.4k points

1 Answer

4 votes

Answer:


f^(-1)(x)= \:\log _7\left(\left(8x-1\right)^3\right)

Step-by-step explanation:


f(x) = \frac{(7^x)^{(1)/(3) }+1}{8}

Let f(x) be y


y = \frac{(7^x)^{(1)/(3) }+1}{8}

exchange x and y


x = \frac{(7^y)^{(1)/(3) }+1}{8}

simplify


8x= {(7^y)^{(1)/(3) }+1}

simplify


8x - 1 = 7^{(y)/(3) }

simplify


8x - 1 = \sqrt[3]{7^y}

simplify


(8x-1)^3 = 7^y

apply log rules


y = (log((8x-1)^3 ))/(log(7))


y = \:\log _7\left(\left(8x-1\right)^3\right)

therefore


f^(-1)(x)= \:\log _7\left(\left(8x-1\right)^3\right)

User Pexichdu
by
4.9k points